2023
DOI: 10.3389/fneur.2023.1058697
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in mitral valve prolapse: risk factors and left atrial function in cryptogenic versus non-cryptogenic ischemic subtypes

Abstract: Background and purposeMitral valve prolapse (MVP) has been associated with an increased risk of ischemic stroke. Older age, thicker mitral leaflets, and significant mitral regurgitation (MR) leading to atrial fibrillation have been traditionally considered risk factors for ischemic stroke in MVP. However, specific risk factors for MVP-stroke subtypes are not well defined. The aim of this study is to evaluate clinical and echocardiographic parameters, including left atrial (LA) function, in MVP with cryptogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…However, this is largely driven by the increased incidence of AF in this population [250,251]. Other studies involving younger patients have not found that MVP is associated with ischaemic stroke, with another study finding that MVPassociated MR is protective against stroke [249,251,252]. Overall, MS is associated with an increased risk of ischaemic stroke, whilst the relationship between MR, MVP, and stroke is less clear.…”
Section: Mitral Valvulopathymentioning
confidence: 93%
See 1 more Smart Citation
“…However, this is largely driven by the increased incidence of AF in this population [250,251]. Other studies involving younger patients have not found that MVP is associated with ischaemic stroke, with another study finding that MVPassociated MR is protective against stroke [249,251,252]. Overall, MS is associated with an increased risk of ischaemic stroke, whilst the relationship between MR, MVP, and stroke is less clear.…”
Section: Mitral Valvulopathymentioning
confidence: 93%
“…However, significant MR may in fact protect against LA spontaneous echo contrast in patients with non-rheumatic AF [244], with other studies finding that MR is neither an additional risk factor nor a protective factor for thromboembolic events in patients with AF [245][246][247]. Mitral valve prolapse (MVP) may be associated with an increased risk of ischaemic stroke, with studies including the Framingham Heart Study suggesting that individuals with MVP may have a slightly elevated risk of embolic events, including stroke [239,[248][249][250]. However, this is largely driven by the increased incidence of AF in this population [250,251].…”
Section: Mitral Valvulopathymentioning
confidence: 99%